Parapharyngeal giant ganglioneuroma with multifocal bone involvement in a pediatric female patient - Salimov, Asif; Süslü, Nilda; Kuşçu, Oğuz; Süslü, Ahmet Emre; Akyol, Mehmet Umut; Gököz, Özay; Özoğul, Ece (The Turkish Journal of Pediatrics, 2016)
Ganglioneuroma is a rare benign tumor that originates from neural crest. Tumor tends to be slow growing, asymptomatic but can cause symptoms because of pressure to neighboring structures. In the head and neck region they are relatively rarely seen. We hereby present a rare case of multiple ganglioneuromas that were located in parapharyngeal space, iliac bone and other bones in a 13-year-old girl. Patient underwent surgery for the excision of a large mass, extending from parapharyngeal space to neck, with transparotid and transcervical combined approach. After operation, MIBG (iodine-123-meta-iodobenzylguanidine) scintigraphy was performed and involvement of parietooccipital bone, lumbal vertebra, right iliac wing medial cortex and left humerus were detected. No adjuvant therapy was given to the patient. There is no evidence of recurrence in the head and neck region in the following 12 months. In conclusion, complete surgical excision of the tumor, if possible, is the treatment of choice with high success rate. Close clinical and radiological follow-up for these tumors after surgery should be made.
Keywords: bone; ganglioneuroma; multifocal; parapharyngeal space; pediatric